The Destination Attributes on the Revisit Intention Mediated by the Destination Image - Rohim, Yasin Nur; Moko, Wahdiyat; Rahayu, Mintarti (Interdisciplinary Social Studies, 2022)
Sharia hotels are an important accommodation needed by tourists in making Muslim travel. East Java has great potential for Muslim tourists with so many destinations available. Thus, the need for Sharia hotel management to be able to compete with conventional hotels and understand consumer satisfaction which in the end makes a re-visit to Sharia hotels. The purpose of this study is to analyze the factors influencing the intention of Muslim tourists to re-visit Sharia hotels in East Java. The destination attribute of a Sharia hotel becomes an exogenous variable that affects the intention to make a revisit with the image of the destination as a mediation variable.  This research is included in explanatory research. Respondents in this study were guests who were or had stayed at Sharia hotels in East Java. The number of samples in this study used purposive sampling techniques with a sample of 148 respondents. The results of the study concluded that the attributes of Islamic destinations have a significant influence on the intention to visit again at Sharia hotels in East Java. Destination image also plays a role in mediating the relationship between destination attributes and returning intentions.